2022
DOI: 10.1002/hbm.26054
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term musical training induces white matter plasticity in emotion and language networks

Abstract: Numerous studies have reported that long‐term musical training can affect brain functionality and induce structural alterations in the brain. Singing is a form of vocal musical expression with an unparalleled capacity for communicating emotion; however, there has been relatively little research on neuroplasticity at the network level in vocalists (i.e., noninstrumental musicians). Our objective in this study was to elucidate changes in the neural network architecture following long‐term training in the musical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…Conversely, loss of function for DNT-2, Toll-6 and kek-6 induced apoptosis, dopaminergic neuron loss, decreased dendritic complexity, impaired targeting, caused synapse loss and impaired locomotion. These phenotypes support previous findings that Toll-6 can promote cell survival and connectivity in development [50] [3] and that together with Kek-6 it promotes synaptogenesis at the larval NMJ [74]. Similarly, Toll-2 is also neuro-protective in the adult fly brain, and loss of Toll-2 function caused neurodegeneration and impaired behaviour [48].…”
Section: A Closed Loop Between Experience and Behaviour Could Drive B...supporting
confidence: 89%
See 2 more Smart Citations
“…Conversely, loss of function for DNT-2, Toll-6 and kek-6 induced apoptosis, dopaminergic neuron loss, decreased dendritic complexity, impaired targeting, caused synapse loss and impaired locomotion. These phenotypes support previous findings that Toll-6 can promote cell survival and connectivity in development [50] [3] and that together with Kek-6 it promotes synaptogenesis at the larval NMJ [74]. Similarly, Toll-2 is also neuro-protective in the adult fly brain, and loss of Toll-2 function caused neurodegeneration and impaired behaviour [48].…”
Section: A Closed Loop Between Experience and Behaviour Could Drive B...supporting
confidence: 89%
“…Importantly, generative structural brain plasticity (e.g. adult neurogenesis, neuronal survival, neurite growth and synaptogenesis) correlates with anti-depressant treatment, learning, physical exercise and well-being [3, 4, 9, 13]. Conversely, structural homeostasis (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…77 These observations align with evidence reported by Rogenmoser et al 78 wherein the brain anatomies of amateur musicians resembled those of people considerably younger, indicating that music engagement may promote 'age-decelerating' effects. Structural brain changes also appear within white matter tracts, with young and middle-aged adult musicians typically possessing enlargement in the corpus callosum 79,80 and widespread differences in white matter organization across frontal, occipital and temporal regions as well as the corticospinal tract and cerebellum [81][82][83][84][85] Preliminary evidence suggests that some of these changes may persist into older age among musicians. 86 Increased functional activity has also been identified in older musicians, whereby enhanced functional activation has been observed in frontotemporal, sensorimotor and parietal networks.…”
Section: Mechanisms Related To Music Engagement In Dementia Preventionmentioning
confidence: 99%
“…Another reason we applied low‐frequency rTMS to the right Broca mirror area is that Cheng et al. (2022) have suggested that long‐term singing is beneficial to the structural remodelling of the left hemisphere. As well, previous research has shown that singing mainly involves language processing, which is left‐lateralised (Knecht et al., 2000).…”
Section: Introductionmentioning
confidence: 99%